Multi-wavelength fiber laser with erbium doped zirconia fiber and semiconductor optical amplifier - Hamzah, Amirah (INOE, 2010)
Multi-wavelength hybrid fiber lasers are demonstrated in both ring and linear cavities using a fabricated Erbium-doped Zirconia fiber (EDZF) and semiconductor optical amplifier (SOA) as gain media. In both configurations, the a fiber loop mirror, which is constructed using a 3 m long polarization maintaining fiber (PMF) and a polarization insensitive 3dB coupler is used as a comb filter for the fiber laser. In the ring cavity, 10 simultaneous lines with peak power above -26 dBm is obtained at 1550 nm region. This is an improvement compared to the linear cavity configuration which has only 5 simultaneous lines observed from wavelength 1556.1 nm to 1563.0 nm with the peak power above -40 dBm. Both hybrid lasers has a constant line spacing of 1.7 nm, which is suitable for wavelength division multiplexing and sensing applications and shows a stable operation at room temperature.